2005
DOI: 10.1158/0008-5472.can-04-4099
|View full text |Cite
|
Sign up to set email alerts
|

Motexafin Gadolinium Disrupts Zinc Metabolism in Human Cancer Cell Lines

Abstract: To gain a better understanding of the mechanism of action of the metal cation-containing chemotherapeutic drug motexafin gadolinium (MGd), gene expression profiling analyses were conducted on plateau phase human lung cancer (A549) cell cultures treated with MGd. Drug treatment elicited a highly specific response that manifested in elevated levels of metallothionein isoform and zinc transporter 1 (ZnT1) transcripts. A549 cultures incubated with MGd in the presence of exogenous zinc acetate displayed synergistic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 55 publications
2
65
0
Order By: Relevance
“…In support of this, zinc administration has been shown to enhance the therapeutic indices of various antineoplastic agents (34,35). Interestingly, zinc by itself has been shown in xenograft models to be an effective antitumoral agent (36,37), as well as being implicated in the mechanism of action of novel therapies (38)(39)(40)(41). There are multiple studies suggesting that zinc addition to chemotherapeutic agents improves their antitumoral capacity, in xenograft models (20,42) as wells as in humans (43,44), and against chemoresistant cells (45).…”
Section: Discussionmentioning
confidence: 94%
“…In support of this, zinc administration has been shown to enhance the therapeutic indices of various antineoplastic agents (34,35). Interestingly, zinc by itself has been shown in xenograft models to be an effective antitumoral agent (36,37), as well as being implicated in the mechanism of action of novel therapies (38)(39)(40)(41). There are multiple studies suggesting that zinc addition to chemotherapeutic agents improves their antitumoral capacity, in xenograft models (20,42) as wells as in humans (43,44), and against chemoresistant cells (45).…”
Section: Discussionmentioning
confidence: 94%
“…[8][9][10] A similar process of electron capture followed by air-based oxidation could also contribute to the induced expression of metallothioneins and altered zinc homeostasis. 11 To the extent such redox-based modes of action are important, it provides an incentive to make and test new texaphyrin derivatives whose electronic properties are modified compared to 1. In this paper, we report the synthesis and preliminary in vitro biological analysis of a new series of gadolinium texaphyrins in which the electron-rich dialkoxydiaminobenzene derivative used in 1 is replaced by diaminonaphthalene and diaminobenzene subunits (compounds 2-5; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, zinc levels have been reported to modulate protein kinase C (8,9), nuclear factor nB (10,11), and p53 (12) activities and signaling pathways relevant to carcinogenesis (13,14). In light of these effects, it is perhaps not surprising that zinc possesses both antiapoptotic or proapoptotic properties that are dependent on intracellular levels (6,15).…”
Section: Introductionmentioning
confidence: 99%
“…MGd is an electron-affinic compound that mediates electron transfer from a variety of intracellular reducing species, such as ascorbate, NADPH, and thiols, to oxygen to form superoxide and hydrogen peroxide (17)(18)(19)(20). Recently, we generated gene expression profiles of plateau phase A549 lung cancer cell cultures treated with MGd and observed marked induction of transcript levels of genes that play major roles in controlling intracellular free zinc levels (6). We also reported that MGd increased intracellular free zinc levels, modulated the cellular toxicity of zinc, and inhibited cellular bioreductive activity in several human cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%